Fibre optic displacement sensor for honey purity detection in distilled water - Nur Nabilah Faiqah Rosli, (Enhanced Knowledge in Sciences and Technology, 2022)
Honey is partly a food substance in flower nectar or other parts of flower plants produced by honey bees cause it to have higher demands in the commercial market. However, since honey is often sold commercially, it causes a bulk of adulterated or fake honey, especially in South East Asia, including Malaysia. This paper reported a simple fibre optic displacement sensor detecting honey purity in distilled water. The sensor detected the purity of honey at different concentrations of honey. Kelulut and Tualang act as pure honey, whereas HoneyBee and EvaBee as adulterated honey demonstrate the sensor's performance. The displacement curves of honey solutions with various concentrations by using FODS system. The pure honey with a higher concentration has greater sensitivity 0.2344 mV/mm for Kelulut and 0.2312 mV/mm for Tualang as it can detect the signal closer to the sensor's sensitivity in the air. However, for adulterated honey, it has increased in sensitivity as the concentration decreased which is for HoneyBee is 0.1901mV/mm and EvaBee is 0.1504mV/mm. The proposed sensor had a real-time measurement, consistent performance, and the most straightforward sensor design, which gives valuable parameters in detecting honey purity.